The Analysis of ESG scores on Malaysian banking performance: a panel data approach - Naufal Shadiq (Ifma Publishing, 2026)
This study study examines the relationship between environmental, social, and governance (ESG) scores and bank performance in Malaysia over 2019–2024. We focus on profitability, measured by return on assets adjusted for risk-weighted assets (ROA RWA), and firm value, proxied by Tobin’s Q. Using a fixed effects framework as the primary specification, complemented by nonlinear and interaction models, we find no statistically significant linear or lagged effect of ESG on profitability or firm value. However, we document a nonlinear (inverted U-shaped) relationship between ESG and firm value, indicating diminishing returns at higher ESG levels. Furthermore, the interaction between ESG and firm size is negative and significant, suggesting that ESG has stronger valuation effects for smaller banks. These findings imply that ESG is not a universally value-enhancing factor but operates through nonlinear and conditional mechanisms. The study contributes to the ESG–banking literature by reconciling mixed prior evidence and highlighting the importance of model specification and firm heterogeneity.